Performance Study of Thin Film Composite Polyamide Membranes in Remediation of Nitro–phenols from Water - Yogesh, K.; Popat, K. M.; Brahmbhatt, H. R.; Ganguly, B.; Bhattacharya, A. (Journal of Applied Membrane Science & Technology, 2017)
Apart from the desalination activities, polyamide membranes spread their wings in different separation arena (viz.removal of organic pollutants, pesticides). The separation abilities of the membranes are basically involved in their compositions as well as nature of the solutes. The study brings to light that the removal of the two isomers of the nitrophenols are based on their orientation (viz. dipolemoment). The prepared membrane compositions are also very interesting to study to be dealt herewith. Molecular sizes and their dipole moments of the corresponding nitrophenols are calculated by quantum chemical method. The rejection performance of the phenol compounds for the same membranes are in the following order: 2–nitro phenol > 4–nitro phenol > phenol.